A visit by University of Queensland’s representative / Nor Azizah Talkis - Talkis, Nor Azizah (Corporate Communication Unit, Universiti Teknologi MARA, Perak Branch, 2018)
UiTM Perak Branch, in its never-ending effort to broaden the horizons for students, had scheduled a meeting with Dr. Paola Leardini, a representative from University of Queensland, Australia, upon her visit to UiTM Perak Branch earlier this February. The aim of this visit was to consider any possible poten-tial collaboration that could be made between UiTM Perak Branch and University of Queensland, concerning the ar-chitecture courses. In accordance, Rector of UiTM Perak, Assoc. Prof. Sr. Dr. Md Yusof Hamid presented the list of accreditations gained by UiTM Perak, to acknowledge the related programmes. Dr. Paola also showed a great interest in other joint ac-tivities, including students exchange, summer camps, lecturers exchange and double-degree programmes. She even suggested several ways to collaborate in re-searches between these two universities.